Islamic Law’s View of Monopoly And Its Impact on Monoplistic Practices in Indonesia - M Soleh Mauludin (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
This research aims to examine how Islamic law views the concept of monopoly, as well as the impact of that view on monopoly practices in Indonesia. Using a descriptive qualitative approach, this study concluded that Islamic law's view of monopoly influences monopoly practices in Indonesia. The practice of monopoly in Indonesia takes the opinion of Islamic law which states that monopolies are allowed as long as it has a positive impact on society. This opinion is then applied in government policy to monopolize certain business areas, where the goal is to meet the needs of the community for primary goods at a reasonable price. The limitation of this study is that it does not analyze other factors that influence the government's monopoly policy. Keywords: Islamic law, monopoly